Large eddy simulation study of the effect of pilot swirler blade angle on the coherent structure in a dual-swirl combustor - FENG Xiangzhou; SUO Jianqin; LI Qiandong; ZHENG Longxi (Xibei Gongye Daxue Xuebao, 2023)
Large-scale coherent structures in a dual-swirl direct-mix combustor and the effect of the pilot swirler blade angle variations (35°, 40° and 45°) on them are investigated by using the large eddy simulations. The results show that no apparent coherent structure is observed downstream of the main swirler, and four typical helical vortex structures are captured downstream of the pilot swirler, representing the PVC and its three higher harmonic modes, respectively. According to the "decoupling" position from the shear layer, the spiral vortex is divided into two regions in space, the "development zone" and the "dissipation zone", respectively. In the frequency domain, as the pilot swirler blade angle increases, the characteristic frequency of the PVC and its higher harmonic structures first decrease and then increase, the energy contribution of the harmonic mode increase, and the double-helix structure replaces the single-helix structure as the dominant structure in the non-constant flow field. In the space domain, as the pilot swirler blade angle increases, the total length of PVC remains basically constant, the initial radius gradually increases, the expansion angle first increases and then decreases, and the position of "decoupling" between shear layer and spiral vortex gradually advances.